The end of the world (Dept. of Performance & Media, 2010)
Three different stories woven together into a half an hour-long film. While a meteor shower heads towards earth, a young man confronts the issues of his past regarding his father. Two best friends who grew up together believing in the healing powers of herbal soup must now face the fact that distance may destroy their special bond, and a son faces up to his parents when he no longer can conform to their strict upbringing.